Optimizing the Directivity of Multiway Loudspeaker Systems. (23rd August 2010) - Shaiek, Hmaied; Boucher, Jean Marc
Abstract : In multiway loudspeaker systems, digital signal processing techniques have been used to correct the frequency response, the propagation time, and the lobbing errors. These solutions are mainly based on correcting the delays between the signals coming from loudspeaker system transducers, and they still show limited performances over the overlap frequency bands. In this paper, we propose an enhanced optimization of relevant directivity characteristics of a multiway loudspeaker system such as the frequency response, the radiation pattern, and the directivity index over an extended transducers' frequency overlap bands. The optimization process is based on applying complex weights to the crossover filter transfer functions by using an iterative approach.